Letter re: Christiansen DH, de Vos Andersen N-B, Poulsen PH, Ostelo RW, The smallest worthwhile effect of primary care physiotherapy did not differ across musculoskeletal pain sites, Journal of clinical epidemiology (2018), doi: 10.1016/j.jclinepi.2018.05.019 - Hancock, M.; Kent, Peter (Elsevier, 2019)
No Abstract Available